Minat Investasi Saham Mahasiswa PTJJ dalam Pasar Modal: Menelusuri Variabel dan Pengaruhnya - Yandes, Jufri; Fadillah, Syarif; Ismulyaty, Sri; Destiana (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study explores the impact of investment knowledge and the use of online investment applications on equity investment interest among PTJJ students of Open University Bandar Lampung through questionnaire statements. In today's digital landscape, technology has opened up new avenues for the younger generation to invest more easily and flexibly. Implementation The study used a quantitative approach with primary data and a survey adopting an ordinalized and modified Likert scale, as well as multiple regression, it was found that investment knowledge significantly increased students' interest in the stock market. Online investment applications also contribute positively by providing a user-friendly and educative platform. This synergy between knowledge and technology strengthens students engagement in equity investment. This study recommends improving financial literacy and technology integration in investment education. Educational institutions are advised to enrich the curriculum with investment materials and organise relevant training. Collaboration with online investment application providers to organise seminars and training can also be an effective strategy to increase students investment interest.